2018
DOI: 10.1097/id.0000000000000820
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Outcomes of Dental Implants Inserted by Flapless or Flapped Procedure

Abstract: This meta-analysis revealed that flapless procedure may increase the failure risk of the dental implants, especially in the situation of immediate/early loading. Nevertheless, flapless procedure showed a superiority in preserving bone tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the same study, the single implants of the test group, which should receive the definitive abutment at the time of surgery, were submitted to a disconnection for the installation of the screw‐retained crown, in the same way as was done for the single and multiple implants of the control group (Molina et al, ). The study by Grandi et al used a technique without flap and immediate loading (Grandi et al, ), which may have influenced peri‐implant marginal bone loss (Zhuang, Zhao, Wu, & Xu, ). In addition, the implants were restored with cement‐retained prostheses, which may undergo interference from other factors such as the presence of luting agent excess in the peri‐implant space (Linkevicius, Puisys, Vindasiute, Linkeviciene, & Apse, ; Linkevicius, Vindasiute, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, the single implants of the test group, which should receive the definitive abutment at the time of surgery, were submitted to a disconnection for the installation of the screw‐retained crown, in the same way as was done for the single and multiple implants of the control group (Molina et al, ). The study by Grandi et al used a technique without flap and immediate loading (Grandi et al, ), which may have influenced peri‐implant marginal bone loss (Zhuang, Zhao, Wu, & Xu, ). In addition, the implants were restored with cement‐retained prostheses, which may undergo interference from other factors such as the presence of luting agent excess in the peri‐implant space (Linkevicius, Puisys, Vindasiute, Linkeviciene, & Apse, ; Linkevicius, Vindasiute, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Grandi et al. used a technique without flap and immediate loading (Grandi et al, 2012), which may have influenced peri-implant marginal bone loss (Zhuang, Zhao, Wu, & Xu, 2018). In addition, the implants were restored with cement-retained prostheses, which may undergo interference from other factors such as the presence of luting agent excess in the peri-implant space (Linkevicius, Puisys, Vindasiute, Linkeviciene, & Apse, 2013;.…”
Section: Discussionmentioning
confidence: 99%
“…These could involve trauma to the surrounding hard and soft tissues during tooth removal [14] or a reduction in alveolar bone because of periodontal or peri-apical pathology. Soft tissue elevation could also have a negative impact on bone preservation, and it is suggested that a flapless surgical approach could reduce the amount of bone loss [15][16][17][18]. It is assumed that alveolar bone remodeling is thus affected by various simultaneous factors, and its magnitude is patient, site and time dependent [19].…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians have attempted every method to prevent MBL and decrease absorption of the buccal bone plate [34][35]. The buccal bone-periodontal ligament (BB-PDL) complex is considered to be very important for maintaining alveolar ridge contour.…”
Section: Discussionmentioning
confidence: 99%